Competencies of Good Parenting in the Islamic Educational Perception - Fawares, Haifa; Al shboul, Asma (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to define a system of competencies for good parenting through the concept of Islamic education. That is through extrapolation of Quranic verses, hadiths and texts in modern references. Methods: The two researchers used a descriptive analytical method in order to achieve this goal. That is through extrapolation of Quranic verses, hadiths and texts to reach a clear conception of good parenting. Results: The results showed that the competencies of good parenting are the sum of the abilities, skills and parenting methods that enable the parent to prepare their children according to the approach of God Almighty. These competencies are divided into areas, which include the religious field represented by sensing the responsibility of raising children, the moral field based on possessing moral qualities that cannot be raised properly without their presence, and specialized educational field. The study also concluded with characteristics of good parenting, which are: knowledge of the characteristics and requirements of children’s growth, and knowledge of education strategies and methods. Conclusion: The study recommends the adoption of the proposal and its inclusion in training programs through training workshops and effective courses that support parents in order to deal with their children in a good manner.